Towards electrode immersion control on lonmin's no 1 circular furnace - Georgalli, G.; Eksteen, Jacques; Bezuidenhout, R.; van Beek, B.; Goff, T. (Southern African Institute of Mining and Metallurgy, 2008)
A control philosophy to be applied by Lonmin to maintain constant electrode immersion in their no. 1 circular smelting furnace is put forward. This control philosophy is facilitated though a combinationof thermodynamic models used to predict the slag composition and empirical correlations to estimate the furnace geometric factor as well as the slag conductivity. The model can determine theoperating resistance setpoint required in order to maintain a desired electrode immersion as a function of the feeds to the furnace, slag level and temperature. If modifying the resistance setpoint cannotmaintain the desired immersion without moving out of the furnace P-V-I operating envelope, the model can be used to determine the amount of slag modifiers (silica or lime) required to shift the slagchemistry back into a region where the immersion can be controlled though resistance setpoint manipulation.